Method for preparing CuCrNb-Incone625 sandwich structure liquid rocket combustion chamber through cold spraying

The preparation of CuCrNb-Inconel625 sandwich structure through cold spraying technology and hot isostatic pressing process solves the problems of low utilization rate of forging materials in liquid rocket combustion chambers and complex diffusion welding methods, and realizes efficient and low-cost sandwich structure preparation, which extends the The engine's service life and enhances the bonding strength of the structure.

CN119194435APending Publication Date: 2024-12-27SHAANXI SIRUI ADVANCED MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411149617.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-21
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The forging and processing methods of existing liquid rocket combustion chambers lead to low material utilization and high cost, and complex diffusion welding methods and high requirements for outer wall dimensional accuracy, which easily leads to softening of the inner wall of copper alloy and affects the number of engine usage.

Method used

The CuCrNb-Inconel625 sandwich structure was prepared by cold spraying technology, and the base layer and Inconel625 alloy layer with a thickness of 20-40mm were prepared through cold spraying technology. Combined with the thermal isostatic pressing process, a dense and uniform sandwich structure was formed, avoiding the waste of forging materials and Complexity of diffusion welding.

Benefits of technology

It improves material utilization and production efficiency, reduces processing costs, retains the mechanical properties of the inner wall of the copper alloy, extends the service life of the liquid rocket engine, and enhances the bonding strength between the Inconel625 alloy layer and the sealing layer through surface treatment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194435A_ABST
    Figure CN119194435A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of cold spraying, in particular to a method for preparing a CuCrNb-Incone625 sandwich structure liquid rocket combustion chamber through cold spraying. Comprising the following steps: S1, preparing CuCr4Nb2 alloy powder into a base layer by adopting a cold spraying process; s2, CuCr4Nb2 alloy powder is sprayed to the surface of the base layer through a cold spraying technology to form a closed layer, and the inner wall of the combustion chamber is obtained; s3, Inconel 625 alloy powder is sprayed to the sealing layer through a cold spraying technology to form an Inconel 625 alloy layer, and a combustion chamber blank is obtained; and S4, performing hot isostatic pressing on the combustion chamber blank to obtain the combustion chamber. The inner wall and the outer wall of the combustion chamber are prepared through the cold spraying technology, compared with a traditional diffusion welding method, the mechanical property of the copper alloy inner wall is reserved, the copper alloy inner wall is prevented from being softened at the welding high temperature, and the service life of a liquid rocket engine is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cold spraying, and in particular to a method for preparing a CuCrNb-Inconel625 sandwich structure liquid rocket combustion chamber by using cold spraying. Background Art

[0002] Liquid rocket engines generate power through the combustion of propellants. The combustion process of propellants mainly takes place in the combustion chamber, which requires the inner wall material of the combustion chamber to have good high temperature resistance and thermal conductivity, and the outer wall to have high strength to ensure the stability of the entire combustion chamber. Generally, the combustion chamber of a liquid rocket is designed as a metal sandwich structure that uses liquid fuel for cooling and regeneration. The inner wall of the sandwich structure has raised ribs and an outer wall travel channel.

[0003] In the prior art, the inner wall of the combustion chamber is forged or spin-formed with copper alloy and then milled, and the outer wall is milled and formed with 316L stainless steel or high-temperature alloy, and then the inner wall and the outer wall of the combustion chamber are connected by diffusion welding. The method of milling after forging leads to low material utilization, long processing cycle and high cost. At the same time, the diffusion welding method has complex equipment and high requirements for the dimensional accuracy of the outer wall. In addition, the high temperature during the welding process can easily soften the copper alloy material, resulting in large residual stress between the inner wall and the outer wall of the copper alloy, which greatly affects the number of times the liquid rocket engine is used. Summary of the invention

[0004] In order to solve the above problems, the present invention provides a method for preparing a CuCrNb-Inconel625 sandwich structure liquid rocket combustion chamber by cold spraying.

[0005] The technical solution of the present invention is: a method for preparing a CuCrNb-Inconel625 sandwich structure liquid rocket combustion chamber by cold spraying, comprising the following steps:

[0006] S1. Using a cold spraying process to form a base layer with a thickness of 20 to 40 mm using CuCr4Nb2 alloy powder, and then machining a groove on the base layer by machining;

[0007] S2, filling the groove with a filler, and then using a cold spray process to spray CuCr4Nb2 alloy powder onto the surface of the base to form a closed layer, thereby obtaining the inner wall of the combustion chamber;

[0008] S3, heating to remove the filler in the groove, and then using a cold spraying process to spray Inconel625 alloy powder onto the closed layer to form an Inconel625 alloy layer to obtain a combustion chamber blank;

[0009] S4. Hot isostatic pressing the combustion chamber blank at 900-1100° C. and 110-130 MPa for 2-4 hours to obtain the combustion chamber.

[0010] Description: The above process uses cold spraying technology to prepare the inner wall of the combustion chamber. Compared with the forging processing method, it improves material utilization and production efficiency and reduces processing costs. The Inconel625 alloy layer is made on the inner wall of the combustion chamber by cold spraying technology as the outer wall. Compared with the traditional diffusion welding method, the mechanical properties of the copper alloy inner wall are retained, the softening of the copper alloy inner wall under high welding temperature is avoided, and the service life of the liquid rocket engine is increased.

[0011] Furthermore, the particle sizes of the CuCr4Nb2 alloy powder and the Inconel625 alloy powder are both 15-45 μm.

[0012] Note: The inner and outer walls of the combustion chamber prepared with powders of the above-mentioned particle size have dense structures, uniform tissues, and fewer internal defects.

[0013] Furthermore, in step S2, the thickness of the sealing layer is 0.1 to 2 mm.

[0014] Note: Defining the thickness of the sealing layer can ensure the connection strength between the inner wall and the outer wall of the combustion chamber, and ensure the thermal conductivity of the inner wall of the combustion chamber.

[0015] Furthermore, in step S3, the thickness of the Inconel625 alloy layer is 2 to 10 mm.

[0016] Note: Limiting the thickness of the Inconel625 alloy layer can ensure the structural strength of the combustion chamber.

[0017] Furthermore, in step S2, the filler is a mixture of paraffin wax and aluminum strips in a weight ratio of 1 to 2:1.

[0018] Note: The cost of using paraffin wax and aluminum strips for filling is low, and they can be removed by heating. The removal process is simple and no residual substances are left.

[0019] Furthermore, the cold spraying process uses argon or nitrogen as the spraying gas.

[0020] Note: Using argon or nitrogen as the spraying gas can ensure that the structure of the inner wall of the combustion chamber is dense, with fewer internal defects, and ensure the bonding strength between the Inconel625 alloy layer and the inner wall of the combustion chamber.

[0021] Further, in step S2, after obtaining the inner wall of the combustion chamber, the inner wall of the combustion chamber is subjected to surface treatment, and the surface treatment method is:

[0022] S2-1, placing the inner wall of the combustion chamber into a lauric acid ethanol solution and soaking for 8 to 12 hours to obtain a pretreated inner wall of the combustion chamber; the mass ratio of lauric acid to anhydrous ethanol in the lauric acid ethanol solution is 1:100 to 120;

[0023] S2-2, adding chromium-plated carbon nanotubes and sodium dodecyl sulfate into anhydrous ethanol, and ultrasonically dispersing for 10 to 20 minutes to obtain a second dispersion; the mass ratio of chromium-plated carbon nanotubes, sodium dodecyl sulfate, and anhydrous ethanol is 1:2 to 5:400 to 600;

[0024] S2-3, using dilute hydrochloric acid with a mass concentration of 10-15% to adjust the pH of the second dispersion to 4-6, and immerse the pretreated inner wall of the combustion chamber in the second dispersion for 1-2 hours. After the immersion is completed, take out the inner wall of the combustion chamber and dry it to obtain the inner wall of the combustion chamber after surface treatment;

[0025] The preparation method of the chromium-plated carbon nanotubes is as follows:

[0026] S2-2.1, adding carbon nanotubes and sodium dodecyl sulfate into anhydrous ethanol, and ultrasonically dispersing for 10 to 20 minutes to obtain a first dispersion; the mass ratio of carbon nanotubes, sodium dodecyl sulfate, and anhydrous ethanol is 1:2 to 5:400 to 600;

[0027] S2-2.2, take an aluminum nitride ceramic plate as a substrate, select one surface of the substrate as a loading surface, put the substrate into the first dispersion for immersion, apply an electric field to the first dispersion during the immersion process, the direction of the electric field is perpendicular to the loading surface, the intensity of the electric field is 60 to 80 V / cm, and after immersion for 0.5 to 1 hour, a substrate loaded with carbon nanotubes is obtained;

[0028] S2-2.3. Lift the substrate loaded with carbon nanotubes so that the loading surface is opposite to the upper surface of the plating solution, then lower the substrate loaded with carbon nanotubes until the loading surface contacts the upper surface of the plating solution, adjust the pH value of the plating solution to 3-4 using a sulfuric acid solution with a mass concentration of 20-30%, then heat the plating solution, after the temperature of the plating solution rises to 70-80°C, keep it warm for 15-25 minutes, add hydrogen peroxide to the plating solution, keep it warm for 1-2 hours again, take out the substrate loaded with carbon nanotubes and scrape off the carbon nanotubes to obtain chrome-plated carbon nanotubes; the amount of hydrogen peroxide added is 0.6-1% of the mass of the plating solution.

[0029] Description: The above method first loads the carbon nanotubes vertically on the loading surface, and then puts one end of the carbon nanotubes into the plating solution for chromium plating. At the same time, one end of the carbon nanotubes will be oxidized in an acidic environment to produce hydroxyl groups. Then the inner wall of the combustion chamber is placed in a mixed solution of lauric acid and anhydrous ethanol to introduce carboxyl groups on the inner wall of the combustion chamber. The hydroxyl groups at one end of the carbon nanotubes can be combined with the carboxyl groups on the inner wall of the combustion chamber. After the hot isostatic pressing process, one end of the carbon nanotubes can react with the pre-plated chromium to generate chromium carbide on the closed layer made of CuCr4Nb2 alloy powder, so that one end of the carbon nanotubes and the closed layer are well bonded. The other end of the carbon nanotubes can react with the nickel in the Inconel625 alloy to generate nickel carbide, so that the other end of the carbon nanotubes and the Inconel625 alloy layer are well bonded, and finally the bonding strength between the Inconel625 alloy layer and the closed layer is improved, so that the inner wall and the outer wall of the combustion chamber form a stable structure.

[0030] Furthermore, in step S2-3, the components of the plating solution include, by weight: 80-90 parts of chromium trioxide, 10-30 parts of sodium sulfite, 1-2 parts of polyvinyl alcohol, 10-30 parts of sodium dihydrogen phosphate, 10-20 parts of sodium citrate, and 1100-1200 parts of deionized water.

[0031] Note: The above-mentioned plating solution can form a dense chromium plating layer with high bonding strength on one end of the carbon nanotube, ensuring that one end of the carbon nanotube can be fully converted into chromium carbide.

[0032] Furthermore, in step S2-2, before the substrate is placed in the first dispersion, the load surface is placed in a sodium hydroxide solution with a mass concentration of 10 to 15% for etching for 30 to 40 minutes.

[0033] Note: After etching with sodium hydroxide, the surface roughness of the loading surface can be increased, so that the loading surface can load more carbon nanotubes.

[0034] The beneficial effects of the present invention are:

[0035] (1) The present invention utilizes cold spraying technology to prepare the inner wall of the combustion chamber, which improves material utilization and production efficiency and reduces processing costs compared to forging processing. The cold spraying technology is used to form an Inconel625 alloy layer as the outer wall on the inner wall of the combustion chamber. Compared with the traditional diffusion welding method, the mechanical properties of the copper alloy inner wall are retained, the softening of the copper alloy inner wall under high welding temperature is avoided, and the service life of the liquid rocket engine is increased.

[0036] (2) The present invention plates chromium at one end of the carbon nanotube and introduces a hydroxyl group, and then introduces a carboxyl group on the inner wall of the combustion chamber, so that the hydroxyl group at one end of the carbon nanotube is combined with the carboxyl group on the inner wall of the combustion chamber. After a hot isostatic pressing process, one end of the carbon nanotube reacts with the chromium plating layer to generate chromium carbide, and the other end of the carbon nanotube reacts with the nickel in the Inconel625 alloy to generate nickel carbide, thereby improving the bonding strength between the Inconel625 alloy layer and the sealing layer, so that the inner wall and the outer wall of the combustion chamber form a stable structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] Figure 1 is a schematic diagram of the combustion chamber structure of Example 1 of the present invention;

[0038] Among them, 1-base layer, 2-groove, 3-sealing layer, 4-Inconel625 alloy layer. DETAILED DESCRIPTION

[0039] In order to further illustrate the method adopted by the present invention and the effect achieved, the technical solution of the present invention will be clearly and completely described in combination with experiments below.

[0040] Example 1: A method for preparing a CuCrNb-Inconel625 sandwich structure liquid rocket combustion chamber by cold spraying, comprising the following steps:

[0041] S1. Using a cold spraying process, CuCr4Nb2 alloy powder is made into a base layer 1 with a thickness of 30 mm, and then grooves 2 are machined on the base layer 1; wherein the grooves 2 are radially distributed on the outer wall of the base layer 1, the depth of the grooves 2 is 5 mm, and the spacing between adjacent grooves 2 is 5 degrees;

[0042] S2, fill the groove 2 with a filler, and then use a cold spraying process to spray CuCr4Nb2 alloy powder onto the surface of the base 1 to form a sealing layer 3, thereby obtaining the inner wall of the combustion chamber; wherein the sealing layer 3 is sleeved on the side wall of the base 1, and the thickness of the sealing layer 3 is 1 mm, and the filler is a mixture of paraffin and aluminum strips in a weight ratio of 1.5:1;

[0043] S3, heating to 70° C. to remove the filler in the groove 2, and then using a cold spraying process to spray Inconel 625 alloy powder onto the sealing layer 3 to form an Inconel 625 alloy layer 4, thereby obtaining a combustion chamber blank; wherein the thickness of the Inconel 625 alloy layer 4 is 6 mm;

[0044] S4, hot isostatic pressing the combustion chamber blank at 1000°C and 120MPa for 3h, and obtain the combustion chamber after hot isostatic pressing. The structure of the combustion chamber is as follows: Figure 1 As shown;

[0045] The particle sizes of the CuCr4Nb2 alloy powder and the Inconel625 alloy powder are both 15-45 μm; the cold spraying process uses argon as the spraying gas.

[0046] Embodiment 2: This embodiment is basically the same as Embodiment 1, except that the thickness of the sealing layer 3 is 0.1 mm.

[0047] Embodiment 3: This embodiment is basically the same as Embodiment 1, except that the thickness of the sealing layer 3 is 2 mm.

[0048] Example 4: This example is basically the same as Example 1, except that the thickness of the Inconel625 alloy layer 4 is 2 mm.

[0049] Example 5: This example is basically the same as Example 1, except that the thickness of the Inconel625 alloy layer 4 is 10 mm.

[0050] Embodiment 6: This embodiment is basically the same as Embodiment 1, except that, in step S2, after the inner wall of the combustion chamber is obtained, the inner wall of the combustion chamber is subjected to surface treatment, and the surface treatment method is:

[0051] S2-1, placing the inner wall of the combustion chamber into a lauric acid ethanol solution and soaking for 10 hours to obtain a pretreated inner wall of the combustion chamber; the mass ratio of lauric acid to anhydrous ethanol in the lauric acid ethanol solution is 1:110;

[0052] S2-2, adding chromium-plated carbon nanotubes and sodium dodecyl sulfate into anhydrous ethanol, and ultrasonically dispersing for 15 minutes to obtain a second dispersion; the mass ratio of chromium-plated carbon nanotubes, sodium dodecyl sulfate, and anhydrous ethanol is 1:3.5:500;

[0053] S2-3, using dilute hydrochloric acid with a mass concentration of 12% to adjust the pH of the second dispersion to 5, and immerse the pretreated inner wall of the combustion chamber in the second dispersion for 1.5 hours. After the immersion is completed, take out the inner wall of the combustion chamber and dry it to obtain the inner wall of the combustion chamber after surface treatment;

[0054] The preparation method of the chromium-plated carbon nanotubes is as follows:

[0055] S2-2.1, adding carbon nanotubes and sodium dodecyl sulfate into anhydrous ethanol, and ultrasonically dispersing for 15 minutes to obtain a first dispersion; the mass ratio of carbon nanotubes, sodium dodecyl sulfate, and anhydrous ethanol is 1:3.5:500; the diameter of the carbon nanotubes is 20-50 nm, and the length is 0.5-3 μm;

[0056] S2-2.2, take an aluminum nitride ceramic plate as a substrate, select one surface of the substrate as a loading surface, put the substrate into the first dispersion for immersion, apply an electric field to the first dispersion during the immersion process, the direction of the electric field is perpendicular to the loading surface, the intensity of the electric field is 70V / cm, and after immersion for 0.75h, a substrate loaded with carbon nanotubes is obtained;

[0057] Before the substrate is placed in the first dispersion, the loading surface is placed in a sodium hydroxide solution with a mass concentration of 12% for etching for 35 minutes;

[0058] The components of the plating solution include, by weight: 85 parts of chromium trioxide, 20 parts of sodium sulfite, 1.5 parts of polyvinyl alcohol, 20 parts of sodium dihydrogen phosphate, 15 parts of sodium citrate, and 1150 parts of deionized water;

[0059] S2-2.3. Lift the substrate loaded with carbon nanotubes so that the loading surface is opposite to the upper surface of the plating solution, then lower the substrate loaded with carbon nanotubes until the loading surface contacts the upper surface of the plating solution, adjust the pH value of the plating solution to 3.5 using a 25% sulfuric acid solution, then heat the plating solution, and after the temperature of the plating solution rises to 75°C, keep it warm for 20 minutes, add hydrogen peroxide to the plating solution, keep it warm for another 1.5 hours, take out the substrate loaded with carbon nanotubes and scrape off the carbon nanotubes to obtain chrome-plated carbon nanotubes; the amount of hydrogen peroxide added is 0.8% of the mass of the plating solution.

[0060] Example 7: This example is basically the same as Example 6, except that the mass ratio of lauric acid to anhydrous ethanol in the lauric acid ethanol solution is 1:100.

[0061] Example 8: This example is basically the same as Example 6, except that the mass ratio of lauric acid to anhydrous ethanol in the lauric acid ethanol solution is 1:120.

[0062] Example 9: This example is basically the same as Example 6, except that the pH of the second dispersion is adjusted to 4 using dilute hydrochloric acid with a mass concentration of 12%.

[0063] Example 10: This example is basically the same as Example 6, except that the pH of the second dispersion is adjusted to 6 using dilute hydrochloric acid with a mass concentration of 12%.

[0064] Example 11: This example is basically the same as Example 6, except that the intensity of the electric field is 60 V / cm.

[0065] Example 12: This example is basically the same as Example 6, except that the intensity of the electric field is 80 V / cm.

[0066] Example 13: This example is basically the same as Example 6, except that a sulfuric acid solution with a mass concentration of 25% is used to adjust the pH value of the plating solution to 3.

[0067] Example 14: This example is basically the same as Example 6, except that a sulfuric acid solution with a mass concentration of 25% is used to adjust the pH value of the plating solution to 4.

[0068] Example 15: This example is basically the same as Example 6, except that the amount of hydrogen peroxide added is 0.6% of the mass of the plating solution.

[0069] Example 16: This example is basically the same as Example 6, except that the amount of hydrogen peroxide added accounts for 1% of the mass of the plating solution.

[0070] Example 17: This example is basically the same as Example 6, except that the ingredients of the plating solution include, by weight: 80 parts of chromium trioxide, 10 parts of sodium sulfite, 1 part of polyvinyl alcohol, 10 parts of sodium dihydrogen phosphate, 10 parts of sodium citrate, and 1100 parts of deionized water.

[0071] Example 18: This example is basically the same as Example 6, except that the ingredients of the plating solution include, by weight: 90 parts of chromium trioxide, 30 parts of sodium sulfite, 2 parts of polyvinyl alcohol, 30 parts of sodium dihydrogen phosphate, 20 parts of sodium citrate, and 1200 parts of deionized water.

[0072] Example 19: This example is basically the same as Example 6, except that the hot isostatic pressing temperature is 900°C.

[0073] Example 20: This example is basically the same as Example 6, except that the hot isostatic pressing temperature is 1100°C.

[0074] Example 21: This example is basically the same as Example 6, except that the hot isostatic pressure is 110 MPa.

[0075] Example 22: This example is basically the same as Example 6, except that the hot isostatic pressure is 130 MPa.

[0076] Example 23: This example is basically the same as Example 1, except that the depth of the groove 2 is 6 mm and the spacing between adjacent grooves 2 is 4 degrees.

[0077] Comparative Example 1: With reference to Example 1, the outer wall is prepared in advance with Inconel 625 alloy, and after the sealing layer 3 is prepared, the inner wall and the outer wall of the combustion chamber are welded together using a diffusion welding process.

[0078] Comparative Example 2: Taking Example 6 as a reference, ordinary carbon nanotubes are used instead of chrome-plated carbon nanotubes.

[0079] Comparative Example 3: Taking Example 6 as a reference, the carbon nanotubes are not loaded on the substrate, but directly placed into the plating solution for overall chromium plating.

[0080] Comparative Example 4: Taking Example 6 as a reference, the substrate is placed in the first dispersion without applying an electric field.

[0081] Experimental Example: In order to explore the influence of the parameters of each embodiment on the performance of the combustion chamber, after the combustion chamber prepared in each embodiment is packaged, the groove area of ​​the combustion chamber is pressurized to perform a breaking pressure test, as follows:

[0082] 1. Investigate the influence of sealing layer and Inconel625 alloy layer thickness on combustion chamber performance

[0083] Using Examples 1 to 5 and Comparative Example 1 as experimental comparisons, the combustion chamber performances of the sealing layer and the Inconel 625 alloy layer with different thicknesses are shown in Table 1 below:

[0084] Table 1 Combustion chamber performance at different thicknesses of sealing layer and Inconel625 alloy layer

[0085] Group Destruction pressure / MPa Example 1 62.4 Example 2 53.2 Example 3 68.7 Example 4 55.8 Example 5 73.1 Comparative Example 1 50.5

[0086] It can be seen from the data in Table 1 that, compared with Examples 1 to 5, as the thickness of the sealing layer and the Inconel625 alloy layer increases, the destruction pressure of the combustion chamber will also increase. However, too thick a sealing layer and an Inconel625 alloy layer will affect the heat dissipation performance of the combustion chamber. Therefore, the thickness of the sealing layer and the Inconel625 alloy layer can be selected as needed in actual production.

[0087] Compared with comparative example 1, when the diffusion welding process is adopted in Example 1, the destruction pressure of the combustion chamber is significantly reduced. This may be because the diffusion welding process leads to the softening of the CuCr4Nb2 alloy. Therefore, the preparation process of Example 1 is better.

[0088] 2. Explore the effect of surface treatment on combustion chamber performance

[0089] Using Examples 1 and 6 and Comparative Examples 2 and 3 as experimental comparisons, the combustion chamber performances obtained under different surface treatments are shown in Table 2 below:

[0090] Table 2 Combustion chamber performance under different surface treatments

[0091]

[0092]

[0093] It can be seen from the data in Table 2 that compared with Examples 1 and 6, the breakdown pressure of the combustion chamber after surface treatment is significantly improved. This may be because the bonding between the Inconel625 alloy layer and the sealing layer is better after surface treatment, so the preparation process of Example 6 is better;

[0094] Compared with Examples 2 and 3, the destruction pressure of the combustion chamber decreased when ordinary carbon nanotubes were used or the carbon nanotubes were chrome-plated as a whole. This may be because when ordinary carbon nanotubes were used, one end of the carbon nanotubes could not be effectively connected to the closed layer, and after the carbon nanotubes were chrome-plated as a whole, the other end of the carbon nanotubes could not be effectively connected to the Inconel625 alloy layer. Therefore, the preparation process of Example 6 is better.

[0095] 3. Investigate the effect of the ratio of lauric acid ethanol solution on the performance of the combustion chamber

[0096] Using Examples 6 to 8 as experimental comparison, the combustion chamber performances under different ratios of lauric acid ethanol solution are shown in Table 3 below:

[0097] Table 3 Combustion chamber performance under different ratios of lauric acid ethanol solution

[0098] Group Destruction pressure / MPa Example 6 71.3 Example 7 70.1 Example 8 69.7

[0099] It can be seen from the data in Table 3 that too high or too low a proportion of lauric acid ethanol solution will lead to a decrease in the destruction pressure of the combustion chamber, and the combustion chamber destruction pressure of Example 6 is the highest. This may be because the lauric acid ethanol solution of Example 6 introduces the most carboxyl groups into the inner wall of the combustion chamber, allowing more carbon nanotubes to adhere to the inner wall of the combustion chamber. Therefore, the proportion of lauric acid ethanol solution selected in Example 6 is optimal.

[0100] 4. Investigate the effect of pH value of the second dispersion on combustion chamber performance

[0101] Using Examples 6 and 9-10 as experimental comparisons, the combustion chamber performances of the second dispersion at different pH values ​​are shown in Table 4 below:

[0102] Table 4 Combustion chamber performance of the second dispersion at different pH values

[0103]

[0104]

[0105] It can be seen from the data in Table 4 that a pH value of the second dispersion that is too high or too low will result in a decrease in the combustion chamber's destruction pressure, and the combustion chamber destruction pressure of Example 6 is the highest. This may be because the reaction between the carboxyl and hydroxyl groups on the inner wall of the combustion chamber is most complete at the pH of Example 6, and therefore the pH value of the second dispersion selected in Example 6 is optimal.

[0106] 5. Investigate the influence of electric field strength on combustion chamber performance

[0107] Using Examples 6, 11-12 and Comparative Example 4 as experimental comparisons, the combustion chamber performance under different electric field strengths is shown in Table 5 below:

[0108] Table 5 Combustion chamber performance under different electric field strengths

[0109] Group Destruction pressure / MPa Example 6 71.3 Embodiment 11 68.9 Example 12 70.3 Comparative Example 4 64.8

[0110] From the data in Table 5, it can be seen that, in comparison between Examples 6, 11, and 12, too high or too low electric field strength will lead to a decrease in the destruction pressure of the combustion chamber, and the combustion chamber destruction pressure of Example 6 is the highest. This may be because the arrangement direction of the carbon nanotubes is the most consistent under the electric field strength of Example 6, so the electric field strength selected in Example 6 is the best;

[0111] Compared with comparative example 4, in Example 6, the destruction pressure of the combustion chamber is significantly reduced after no electric field is applied. This may be because after no electric field is applied, the carbon nanotubes are arranged in a disordered manner, resulting in the inability to plate chromium on one end of the carbon nanotubes. Therefore, the preparation process of Example 6 is better.

[0112] 6. Investigate the effects of coating solution pH value, hydrogen peroxide addition, and coating solution composition on combustion chamber performance

[0113] Using Examples 6, 13 to 18 and Comparative Example 5 as experimental comparisons, the combustion chamber performances under different pH values ​​of the plating solution, different amounts of hydrogen peroxide added, and different components of the plating solution are shown in Table 6 below:

[0114] Table 6 Combustion chamber performance under different pH values ​​of the coating solution, different amounts of hydrogen peroxide added, and different compositions of the coating solution

[0115]

[0116]

[0117] It can be seen from the data in Table 6 that, compared with Examples 6 and 13 to 16, the pH value of the plating solution is too high or too low, and the amount of hydrogen peroxide added is too high or too low, which will lead to a decrease in the destruction pressure of the combustion chamber, and the combustion chamber destruction pressure of Example 6 is the highest. This may be because the pH value of the plating solution is too low or the amount of hydrogen peroxide added is too high, which will lead to excessive oxidation of the carbon nanotubes and damage to the carbon nanotube structure. The pH value of the plating solution is too high or the amount of hydrogen peroxide added is too low, which will lead to insufficient introduction of hydroxyl groups on the carbon nanotubes. Therefore, the pH value of the plating solution and the amount of hydrogen peroxide added selected in Example 6 are both optimal;

[0118] Compared with Examples 6, 17 and 18, the combustion chamber destruction pressure of Example 6 is the highest. This may be because the coating formed by the coating solution of Example 6 is the most uniform and has the densest structure. Therefore, Example 6 selects the best coating solution composition.

[0119] 7. Investigate the influence of hot isostatic pressing parameters on combustion chamber performance

[0120] Using Examples 6 and 19 to 22 as experimental comparisons, the performance under different hot isostatic pressing parameters is shown in Table 7 below:

[0121] Table 7 Combustion chamber performance under different hot isostatic pressing parameters

[0122] Group Destruction pressure / MPa Example 6 71.3 Embodiment 19 68.6 Embodiment 20 69.8 Embodiment 21 68.2 Embodiment 22 70.2

[0123] It can be seen from the data in Table 7 that hot isostatic pressing that is too high or too low, or that is too high or too low, will lead to a decrease in the destruction pressure of the combustion chamber, and the combustion chamber destruction pressure of Example 6 is the highest. This may be because the combustion chamber structure is uniform and has fewer defects under the hot isostatic pressing parameters of Example 6, and therefore the hot isostatic pressing parameters selected in Example 6 are optimal.

Claims

1. A method for preparing a CuCrNb-Inconel625 sandwich structure liquid rocket combustion chamber by cold spraying, characterized in that: The following steps are involved: S1, using a cold spraying process to form a base layer (1) with a thickness of 20 to 40 mm using CuCr4Nb2 alloy powder, and then machining a groove (2) on the base layer (1); S2, filling the groove (2) with a filler, and then using a cold spraying process to spray CuCr4Nb2 alloy powder onto the surface of the base layer (1) to form a closed layer (3), thereby obtaining the inner wall of the combustion chamber; S3, heating to remove the filler in the groove (2), and then using a cold spraying process to spray Inconel625 alloy powder onto the sealing layer (3) to form an Inconel625 alloy layer (4), thereby obtaining a combustion chamber blank; S4. Hot isostatic pressing the combustion chamber blank at 900-1100° C. and 110-130 MPa for 2-4 hours to obtain the combustion chamber.

2. The method for preparing a CuCrNb-Inconel625 sandwich structure liquid rocket combustion chamber by cold spraying according to claim 1, characterized in that: The particle sizes of the CuCr4Nb2 alloy powder and the Inconel625 alloy powder are both 15-45 μm.

3. The method for preparing a CuCrNb-Inconel625 sandwich structure liquid rocket combustion chamber by cold spraying according to claim 1, characterized in that: In step S2, the thickness of the sealing layer (3) is 0.1-2 mm.

4. The method for preparing a CuCrNb-Inconel625 sandwich structure liquid rocket combustion chamber by cold spraying according to claim 1, characterized in that: In step S3, the thickness of the Inconel 625 alloy layer (4) is 2 to 10 mm.

5. The method for preparing a CuCrNb-Inconel625 sandwich structure liquid rocket combustion chamber by cold spraying according to claim 1, characterized in that: In step S2, the filler is a mixture of paraffin wax and aluminum strips in a weight ratio of 1 to 2:

1.

6. The method for preparing a CuCrNb-Inconel625 sandwich structure liquid rocket combustion chamber by cold spraying according to claim 1, characterized in that: The cold spraying process uses argon or nitrogen as the spraying gas.

7. The method for preparing a CuCrNb-Inconel625 sandwich structure liquid rocket combustion chamber by cold spraying according to claim 1, characterized in that: In step S2, after the inner wall of the combustion chamber is obtained, the inner wall of the combustion chamber is subjected to surface treatment, and the surface treatment method is as follows: S2-1, placing the inner wall of the combustion chamber into a lauric acid ethanol solution and soaking for 8 to 12 hours to obtain a pretreated inner wall of the combustion chamber; the mass ratio of lauric acid to anhydrous ethanol in the lauric acid ethanol solution is 1:100 to 120; S2-2, adding chromium-plated carbon nanotubes and sodium dodecyl sulfate into anhydrous ethanol, and ultrasonically dispersing for 10 to 20 minutes to obtain a second dispersion; the mass ratio of chromium-plated carbon nanotubes, sodium dodecyl sulfate, and anhydrous ethanol is 1:2 to 5:400 to 600; S2-3, using dilute hydrochloric acid with a mass concentration of 10-15% to adjust the pH of the second dispersion to 4-6, and immerse the pretreated inner wall of the combustion chamber in the second dispersion for 1-2 hours. After the immersion is completed, take out the inner wall of the combustion chamber and dry it to obtain the inner wall of the combustion chamber after surface treatment; The preparation method of the chromium-plated carbon nanotubes is as follows: S2-2.1, adding carbon nanotubes and sodium dodecyl sulfate into anhydrous ethanol, and ultrasonically dispersing for 10 to 20 minutes to obtain a first dispersion; the mass ratio of carbon nanotubes, sodium dodecyl sulfate, and anhydrous ethanol is 1:2 to 5:400 to 600; S2-2.2, take an aluminum nitride ceramic plate as a substrate, select one surface of the substrate as a loading surface, put the substrate into the first dispersion for immersion, apply an electric field to the first dispersion during the immersion process, the direction of the electric field is perpendicular to the loading surface, the intensity of the electric field is 60 to 80 V / cm, and after immersion for 0.5 to 1 hour, a substrate loaded with carbon nanotubes is obtained; S2-2.

3. Lift the substrate loaded with carbon nanotubes so that the loading surface is opposite to the upper surface of the plating solution, then lower the substrate loaded with carbon nanotubes until the loading surface contacts the upper surface of the plating solution, adjust the pH value of the plating solution to 3-4 using a sulfuric acid solution with a mass concentration of 20-30%, then heat the plating solution, after the temperature of the plating solution rises to 70-80°C, keep it warm for 15-25 minutes, add hydrogen peroxide to the plating solution, keep it warm for 1-2 hours again, take out the substrate loaded with carbon nanotubes and scrape off the carbon nanotubes to obtain chrome-plated carbon nanotubes; the amount of hydrogen peroxide added is 0.6-1% of the mass of the plating solution.

8. The method for preparing a CuCrNb-Inconel625 sandwich structure liquid rocket combustion chamber by cold spraying according to claim 7, characterized in that: In step S2-3, the components of the plating solution include, by weight: 80-90 parts of chromium trioxide, 10-30 parts of sodium sulfite, 1-2 parts of polyvinyl alcohol, 10-30 parts of sodium dihydrogen phosphate, 10-20 parts of sodium citrate, and 1100-1200 parts of deionized water.

9. The method for preparing a CuCrNb-Inconel625 sandwich structure liquid rocket combustion chamber by cold spraying according to claim 7, characterized in that: In step S2-2, before the substrate is placed in the first dispersion, the load surface is placed in a sodium hydroxide solution with a mass concentration of 10 to 15% for etching for 30 to 40 minutes.